Antibiotic Prescription Practice for Pediatric Urinary Tract Infection in a Tertiary Center. (4th October 2017) - Alghounaim, Mohammad; Ostrow, Olivia; Timberlake, Kathryn; Richardson, Susan E; Science, Michelle
Abstract: Background: Urinary tract infection (UTI) is a leading cause for acute care visits in pediatrics. A suspected UTI diagnosis is made based on typical clinical presentation and pyuria and confirmed by significant growth in an appropriate urine sample. Prescribing antibiotics for suspected UTI is a common practice, and may lead to unnecessary antibiotic exposure. We aimed to review the practice of UTI diagnosis and management in the Emergency Department (ED) to identify targets to improve antimicrobial prescribing practices. Methods: Children (< 18 years) who were discharged from the ED at the Hospital for Sick Children with a diagnosis of UTI between October to December 2016 were included. Patients were excluded if they were (1) under 12 weeks of age, (2) had underlying genitourinary abnormalities, (3) were admitted or transferred to another center, (4) were on antibiotics on presentation, (5) had urine testing done in another laboratory, or (6) were given conditional prescription. Demographic, clinical history, laboratory findings, and urine culture results were collected from patient charts. The sensitivity and specificity of nitrite and leukocyte esterase (LE) for UTI diagnosis were calculated. Logistic regression was used to examine the relationship between urinalysis characteristics and confirmed UTI. Results: A total of 186 children with a median age of 4.2 (IQR 1.2, 7.3) were included; 82.3% were female. Almost all children were discharged home on antibiotics ( n = 183, 98%) for a median duration of 7 days (IQR 7, 10). A total of 87 patients (46.8%) received antibiotics despite negative urine cultures and none of these patients received notification to stop. This led to 652 unnecessary antibiotic days. The presence of nitrites was the strongest predictor of UTI (OR 13.3, P < 0.001) and was highly specific. An LE result of 2+ (OR 2.4, P = 0.04) or 3+ (OR 2.23, P = 0.016) was also predictive of UTI. Conclusion: Current practice in managing suspected pediatric UTIs in our ED resulted in significant and unnecessary antibiotic exposure. We identified targets to reduce unnecessary antibiotic exposure including improving the diagnostic accuracy of UTIs, a process to discontinue antibiotics for negative cultures and standardizing antimicrobial duration. Disclosures: All authors: No reported disclosures.